O ensino de Filosofia à luz do pensamento de Edith Stein: um relato da prática de oficinas filosóficas como itinerário para a vivência empática - AGUIAR, Wayner de Andrade Lima de (2023)
This dissertation aims to reflect on the problem of teaching, especially the teaching of Philosophy, and its impact on the formation of the student as a person, a member of a community. To this end, I resort to the philosophical and anthropological thought of Edith Stein, as a primary inspiration, in addition to other authors who have dedicated themselves to the issue of teaching and formation of the person. Throughout his work, Stein proposes an educational vision that takes up, in several aspects, the Christian conception of education for human fullness, while remaining faithful to its phenomenological roots. From this union emerges an educational vision that seeks to reach the inner core of the person to lead him to the fullness of his development as a person, making him become what he should become. Inspired by Stein's vision, I analyze what I think are the main points of difficulty in the process of teaching Philosophy, mainly the issue of interpersonal relationships, and based on these, I propose a reflection on how the teaching of Philosophy, seen as an itinerary, can provide the solution or mitigation of such problems, using the model of philosophical workshops as a means for the practice of classes that provide the interpersonal and philosophical experience adequate to the human growth of the students. The questions and problems pointed out in this text are the result of concerns generated in my teaching practice. They arise from the objective experience in the classroom, from the countless problem situations, from all the joys and lessons learned.